The short subjective well-being scale - new instrument for measurement of positive mental health - Jovanović, Veljko; Novović, Zdenka (Primenjena psihologija, 2008)
Subjective well-being is one of the most investigated constructs in the field of positive psychology and one of the most important indicators of positive mental health. An important aim of research in this field is improvement and construction of new measures of subjective well-being. In this article we report on development and validation of the Short Subjective Well-Being Scale (KSB). This scale consists of 8 items, with high internal consistency (a=0,86). Principal components analysis showed that the scale measures two dimensions - affective (Positive Affectivity) and cognitive (Positive Attitude Towards Life). Results suggested that these two dimensions represent different aspects of subjective well-being, which are encompassed by a higher-order factor of subjective well-being. Our results supporting convergent validity of the scale were as follows: significant positive correlations with measures of positive affect, joviality, self-assurance (SIAB-PANAS), and significant negative correlations with measures of anxiety (STAI-T), dysphoria (BDI-II), and negative affect (SIAB-PANAS). Research, clinical, and practical implications of the findings were discussed.